Sociodemographic and clinical characteristics of patients with violence attempts with psychotic disorders. Issue 4 (October 2017) - Korkmaz, Sevda; Turhan, Levent; İzci, Filiz; Sağlam, Sadullah; Atmaca, Murad
No abstract available